Promoting Cultural Awareness through Virtual Learning: A Framework for Textile Artifact Restoration Education (Journal of Global Humanities and Social Sciences, 2025)
This study explores the integration of virtual learning technologies with textile artifact restoration education to promote cultural awareness. Textile artifacts, as a crucial component of cultural heritage, face challenges such as deterioration, limited public access, and under representation in education. Virtual learning, particularly through VR/AR and 3D modeling, offers transformative potential for overcoming these challenges by creating interactive and immersive experiences. Drawing on a mixed-methods approach, the research evaluates how interactivity and immersion serve as mediators in enhancing user engagement and cultural awareness. Quantitative data from surveys and behavioral logs, combined with qualitative insights from interviews and case studies, reveal significant improvements in users’ understanding of textile heritage, emotional connection to cultural narratives, and advocacy for cultural preservation. The findings introduce a hands-on restoration framework, bridging traditional craftsmanship with modern technological advancements. Practical implications include actionable design guidelines for digital museums and educational institutions, emphasizing interactive tutorials, simplified interfaces, and culturally tailored content. Future research should prioritize cross-cultural validation, longitudinal studies, and technological innovation to ensure scalability and sustainability.